Desfase entre los lineamientos del programa de educación de la sexualidad del ministerio de educación del Ecuador y la realidad del mundo infantil en niños de educación básica - Yépez Salazar, Carla Gabriela (2013)
Based on multiple regulations, nationals and internationals, the Ecuadors Ministery of Education has the requirement to provide sex education programs to levels ranging from pre-primary to secundary. In light of this Programa Nacional de Educación de la Sexualidad y el Amorr (PROMESA), proposed a sexuality educations curriculum for the National Education System. According to information provided by Minstery of Educations that was proposed. However, there is inconsistency in the information provided by a confusing speech presented by the Ministrys officials, who argue that even educational institutions use this program as a guide for their planning, at the same time they must not use it fully because, as its content is stale, to use the curriculum would be prohibited